2020
DOI: 10.5888/pcd17.190350
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Immunization Registry Data to Identify Places With Low Rates of HPV Vaccination Initiation in a Rural State

Abstract: Covariate-adjusted initiation rates for human papillomavirus vaccination in zip code tabulation areas (ZCTAs) among adolescents aged 13 to 15, Iowa, 2016. Rates were spatially smoothed to account for small populations. The state-level mean vaccination rate for all ZCTAs was 47.9% (range, 0%-100%; standard deviation, 16.2%). All ZCTAs have initiation rates below the Healthy People 2020 target of 80% completion. Urban ZCTAs are indicated in black outlines. Vaccination initiation rates exhibit no clear associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…Given the positive association between population density and vaccination coverage, there may be a need to focus on increasing HPV vaccination among rural populations. Although other studies have highlighted lower uptake in rural areas (15), this study shows the quantitative relationship between population density and vaccination completion, which has not been previously reported. The inverse association between average number of vehicles per household and vaccination coverage could reflect what we see with the population density effect, as households in urban areas likely have lower vehicle ownership.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Given the positive association between population density and vaccination coverage, there may be a need to focus on increasing HPV vaccination among rural populations. Although other studies have highlighted lower uptake in rural areas (15), this study shows the quantitative relationship between population density and vaccination completion, which has not been previously reported. The inverse association between average number of vehicles per household and vaccination coverage could reflect what we see with the population density effect, as households in urban areas likely have lower vehicle ownership.…”
Section: Discussioncontrasting
confidence: 89%
“…In addition, McKillop and colleagues (14) found that adolescent females A strength of this study is the Bayesian spatial modeling approach allowing for estimation of the probabilities of vaccination of girls and boys independently as well as simultaneously in a model that permits them to be correlated. This is an innovation in the HPV vaccination literature, where separate models have been used for boys and girls (13), or boys and girls have been combined into one outcome variable (15). In addition, we identified the geographic areas of significantly lowered vaccination coverage, which has not been done in other geospatial analyses of HPV vaccination (13,15,32).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations